2012
DOI: 10.1007/s11211-012-0147-x
|View full text |Cite
|
Sign up to set email alerts
|

The Process Matters: Fairness in Repository Siting For Nuclear Waste

Abstract: Siting contested infrastructure such as repositories for nuclear waste very often faces strong local resistance. One major reason for this opposition may arise because siting processes do not appropriately consider fairness issues such as transparency, the availability of options, or the sufficient involvement of concerned and affected people. The aim of this study was to analyze people's concerns related to justice in siting nuclear waste. Besides procedural aspects, both distributive justice and outcome vale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…As shown by McComas et al ., acceptance of induced earthquakes increases when public engagement is possible. Communication efforts should thus not only include and empirically test written communication material as in this study, but also pay close attention to values, concerns, procedural fairness and trust …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by McComas et al ., acceptance of induced earthquakes increases when public engagement is possible. Communication efforts should thus not only include and empirically test written communication material as in this study, but also pay close attention to values, concerns, procedural fairness and trust …”
Section: Discussionmentioning
confidence: 99%
“…First, the communication of uncertainty should be further thought through and empirically tested so that practitioners can get access to robust guidelines of how to communicate transparently without unnecessarily inflating concern or frustration. Second, beyond the careful wording, risk communication for induced seismicity should be researched and empirically tested considering broader, contextual factors, such as the procedural fairness, siting procedures, and attitudes towards projects . Third, risk communication materials could be further tested for other technologies or risks, such as nuclear power, climate change, genetically modified food, in order to produce generalizable insight for science and risk communication.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one can argue that similar conflict patterns could emerge, and of course, societal processes matter. Previous research shows that how a siting process is organized will have an impact on the perceived fairness of the entire process (Krütli et al, 2010(Krütli et al, , 2012. In turn, it will influence how the public reacts, which strategy activist groups will follow (Parthasarathy, 2010).…”
Section: Public Perception Of Deep Geothermal Energymentioning
confidence: 99%
“…It has been widely acknowledged and empirically shown that, in addition to having a fair outcome (as, e.g., in the distribution of burdens and benefits), what very much matters is having a fair procedure in decision making. (35)(36)(37) In social acceptance studies, the relevance of "procedural justice" issues has also been acknowledged, leading to a growing body of work on the participatory approach to decision making in regard to new technologies. (38)(39)(40)(41)(42) Indeed, it is now common practice to recognize a normative rationale for participation as a political right for citizens; (e.g., 41) "the case for participation should begin with a normative argument that a purely technocratic orientation is incompatible with democratic ideals."…”
Section: Social Acceptance and Neglected Ethical Issuesmentioning
confidence: 99%